2023
DOI: 10.33225/pec/23.81.374
|View full text |Cite
|
Sign up to set email alerts
|

Humor Development in Preschool and Primary School Children in Turkiye

Abstract: Knowing humor development can be rather beneficial in terms of providing opportunities to better know children and evaluate their development. This study aimed to explore the process of humor development in preschool and primary school children in line with McGhee's humor development theory. The study employed a single screening model, specifically one of the commonly used screening models in general practice. The study group consisted of 101 children ranging in age from 2 to 11. Research data were collected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…When the literature was examined, it was seen that studies on humor styles were predominant in the studies conducted with teachers (Altınkurt & Yılmaz, 2011;Uyanık et al, 2015;Yılmaz, 2023), while studies on preschool teachers' use of humor and humor styles in the educational environment were limited. Although there are limited studies in which preschool children produce humor and appreciate the value of humor (Eskidemir Meral & Koçer, 2023;Hoicka, & Akhtar, 2011;Loizou, 2007;McGhee, 1971;Stenius et al, 2022), there is no study examining the relationship between preschool teachers' sense of humor and children's appreciation of the value of humor. Based on the view that it is important for children to be exposed to humor for their humor development (Eskidemir Meral & Koçer, 2023) and that teachers' having a sense of humor will contribute to the development of humor in children (Franzini, 2002), it was considered necessary to conduct this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the literature was examined, it was seen that studies on humor styles were predominant in the studies conducted with teachers (Altınkurt & Yılmaz, 2011;Uyanık et al, 2015;Yılmaz, 2023), while studies on preschool teachers' use of humor and humor styles in the educational environment were limited. Although there are limited studies in which preschool children produce humor and appreciate the value of humor (Eskidemir Meral & Koçer, 2023;Hoicka, & Akhtar, 2011;Loizou, 2007;McGhee, 1971;Stenius et al, 2022), there is no study examining the relationship between preschool teachers' sense of humor and children's appreciation of the value of humor. Based on the view that it is important for children to be exposed to humor for their humor development (Eskidemir Meral & Koçer, 2023) and that teachers' having a sense of humor will contribute to the development of humor in children (Franzini, 2002), it was considered necessary to conduct this study.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are limited studies in which preschool children produce humor and appreciate the value of humor (Eskidemir Meral & Koçer, 2023;Hoicka, & Akhtar, 2011;Loizou, 2007;McGhee, 1971;Stenius et al, 2022), there is no study examining the relationship between preschool teachers' sense of humor and children's appreciation of the value of humor. Based on the view that it is important for children to be exposed to humor for their humor development (Eskidemir Meral & Koçer, 2023) and that teachers' having a sense of humor will contribute to the development of humor in children (Franzini, 2002), it was considered necessary to conduct this study. In this context, the study is expected to contribute to the literature.…”
Section: Introductionmentioning
confidence: 99%
“…a. Live The study of Eskidemir Meral andKoçer (2023) revealed that children's exposure to jokes enables them to create humor. In this context, it is thought that including humor situations with various characteristics suitable for different age groups in cartoons will contribute to children's humor development.In stage 2, it is seen that the most humor elements are found in Masha and the Bear, and the least humor elements are found in Keloğlan Masalları.…”
mentioning
confidence: 99%